THE EFFECT OF COMPANY CHARACTERISTICS ON CORPORATE SOCIAL RESPONSIBILITY IN PT. ANGKASA TEMPLE II - Afifah Zahrol Hayat; Nunik Nurmalasari (STIESA Press, 2021)
Corporate Social Responsibility (CSR) is basically a need for companies to be able to interact with the community around the company. The company needs to adapt and to get social benefits from interacting with the surrounding community in the form of trust. CSR is certainly very closely related to corporate culture and business ethics that must be possessed by corporate culture, because to implement CSR itself requires a culture based on adaptive ethics. This research is a descriptive verification study, with a quantitative approach. The population used in this study is the financial statements of PT. ANGKASA PURA II since Go Public. Based on the sampling criteria in this study are financial statements from 2014-2018. Data collection techniques used in this study are documentation techniques by collecting and utilizing data that has been available as a source of information. The data used are secondary data in the form of annual reports (annual report) and financial reports (financial report) of PT. Angkasa Pura II, which has been published. The dependent variable in this study is the disclosure of corporate social responsibility (Corporate Social Responsibility). The independent variables in this study are company characteristics which are proxied by company size (size), profitability, leverage, and company growth. Company size, profitability, leverage, and company growth have no effect on Corporate Social Responsibility. Overall, the results of this study that size, profitability, leverage and growth variables do not affect corporate social responsibility.